2019
DOI: 10.1038/s41415-019-0148-3
|View full text |Cite
|
Sign up to set email alerts
|

The oral health of dentally anxious five- and eight-year-olds: a secondary analysis of the 2013 Child Dental Health Survey

Abstract: If citing, it is advised that you check and use the publisher's definitive version for pagination, volume/issue, and date of publication details. And where the final published version is provided on the Research Portal, if citing you are again advised to check the publisher's website for any subsequent corrections.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
15
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(17 citation statements)
references
References 18 publications
(26 reference statements)
2
15
0
Order By: Relevance
“…Behavior in previous dental appointments may help predict child behavior and emotional reactions in the next dental appointment. In this study, a statistically significant association was found between child behavior during dental care and dental anxiety, in accordance with previous studies [7,17]. Children with uncooperative behavior during previous dental appointments and in current dental appointment had higher dental anxiety prevalence than those with cooperative behavior.…”
Section: Discussionsupporting
confidence: 92%
See 4 more Smart Citations
“…Behavior in previous dental appointments may help predict child behavior and emotional reactions in the next dental appointment. In this study, a statistically significant association was found between child behavior during dental care and dental anxiety, in accordance with previous studies [7,17]. Children with uncooperative behavior during previous dental appointments and in current dental appointment had higher dental anxiety prevalence than those with cooperative behavior.…”
Section: Discussionsupporting
confidence: 92%
“…The family environment has been considered as another important factor associated with dental anxiety in children. Dentally anxious children are less likely of having poor oral health and poor oral health behaviors, such as not going to the dentist for regular dental examinations and to brush teeth twice a day [7].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations